Reviewing Vietnam's Nationally Determined Contribution: A New Perspective Using the Marginal Cost of Abatement - Escobar Carbonari, Daniel; Grosjean, Godefroy; Läderach, Peter; Nghia, Tran Dai; Sander, Bjoern Ole; McKinley, Justin; Sebastian, Leocadio; Tapasco, Jeimar (Frontiers in Sustainable Food Systems, 2019)
The processes countries use to revise their Nationally Determined Commitments (NDCs) under the UNFCCC’s Paris Agreement will be key to ensure that their pledges give effective climate change policy. In many developing countries, the agriculture, forestry and other land use (AFOLU) sector is central to their NDCs. We generated a marginal abatement cost (MAC) curve for Vietnam’s AFOLU sector and used it to review the country’s mitigation pledges for this sector. We conclude that Vietnam could increase the emission pledges in its NDC, especially in future land use. Other options for mitigation at negative cost include water techniques in rice, agroforestry and management of livestock diets and manure. The MAC curve alone is insufficient to prioritize policy options for climate change policy, however, because it underestimates adaptation co-benefits, for example, in protected mangrove systems